Customizing Volume Phase Transition of Thermo‐Responsive Hydrogels. Issue 1 (7th June 2019) - Yoon, Jinhwan
Abstract : To tune the volume phase transition of poly( N ‐isopropylacrylamide) (PNIPAm)‐based hydrogels, the chemical structure of the hydrogels is modified. A shift in the transition temperature, stepwise transition over a wide temperature range, and large thermal hysteresis for the crosslinked hydrogels could be achieved by copolymerization with hydrophobic or hydrophilic comonomers, preparation of multi‐component compositions, and grafting PNIPAm onto methylcellulose, respectively.